การออกเสียงภาษาอังกฤษที่มีสำเนียงแตกต่างกันในภูมิภาคภาษาอาเซียน DIFFERENT ACCENT IN ENGLISH PRONUNCIATION OF ASEAN LANGUAGE AREA - ทาวงศ์ษา, กิตติพัฒน์ (วารสารศรีล้านช้างปริทรรศน์; Vol 4 No 1 (2018): วารสารศรีล้านช้างปริทรรศน์ ปีที่ 4 ฉบับที่ 1 (มกราคม - มิถุนายน 2561), 2018)
จากการเปิดสมาคมอาเซียนในปี 1998 ภาษาอังกฤษได้กลายมาเป็นภาษาที่คนในกลุ่มประเทศอาเซียนต้องใช้ติดต่อสื่อสารในการทำงานร่วมกัน อย่างไรก็ตามพบว่า การใช้ภาษาอังกฤษของคนในอาเซียนมักจะมีเอกลักษณ์เฉพาะตัวเนื่องจากมีการผสมผสานสำเนียงแม่เข้ากับการพูดคำภาษาอังกฤษ ซึ่งทำให้การออกเสียงภาษาอังกฤษแตกต่างจากสำเนียงภาษาอังกฤษทั่วไป แต่ในด้านภาษาศาสตร์แล้วก็ถือว่าไม่มีถูกหรือผิดสำหรับการเรียนรู้ภาษาใดภาษาหนึ่งของคนที่ไม่ใช่เจ้าของภาษา อย่างไรก็ตามหัวใจของการสื่อสารไม่ว่าจะด้วยภาษาอังกฤษหรือภาษาใด ๆ ก็ตามอยู่ที่การสื่อความหมายได้ถูกต้องเข้าใจกันระหว่างผู้พูดและผู้ฟัง การพูดภาษาอังกฤษแบบไทย ๆ หรือที่เรียกว่า ทิงลิช หรือ ไทยลิช รวมไปถึงการพูดภาษาอังกฤษของชาวฟิลิปปินส์ แม้จะเป็นการใช้ภาษาอังกฤษที่ผิดไปจากเดิม แต่ผู้ฟังที่พูดภาษาอังกฤษก็พอจะเข้าใจได้ ซึ่งก็ถือว่าบรรลุเป้าหมายของการสื่อสารแล้ว ดังนั้นการเข้าใจการพูดของสำเนียงต่าง ๆ ส่วนหนึ่งขึ้นอยู่กับการแสวงหาความรู้ และความเคยชินในการฟังสำเนียงเหล่านั้นของผู้พูดเอง จะทำให้เข้าใจความหมายและประสบผลสำเร็จในการสื่อสารของทั้งผู้ส่งสาร และผู้รับสาร               Apart from ASEAN Economic Community in 1998, English became the working language among workers in ASEAN countries. Generally, English spoken by ASEAN people seemed absolutely unique due to mixture of their mother tongue and English. As a result, English pronunciation by ASEAN people looked very different from English-speaking persons around the world. Linguistically, such an event was not regarded right or wrong for non-native speakers to study other foreign languages because the communication, either in English or any language, was importantly focused on right meaning transformation between a speaker and a listener. Different from Standard English, English spoken by Thai people, as known Tinglish or Thailish, including English spoken by Filipino people, was acceptable if it were understood by other English-speaking people. That was really the target of communication. However, understanding various accents was partly depended upon knowledge search and accent familiarity, which were regarded as the basic to understand the meaning and to succeed in communication between a message sender and a message receiver.